Service Learning Program in Tijarah Pintar Gallery, Johor Bahru - Malaysia - Azra Ayue Binti Abdul Rahman; Irmawati Binti Norazman; Siti Aisyah Binti Panatik; Octojaya Abriyoso; Muhamad Rizki Maulana; Fillika Millenia; Fitri Amanda Syahria (Lembaga Pengembangan Kinerja Dosen, 2024)
This article is the result of community service activities. The focus of this activity is an effort to bridge the learning of Malay Arabic script / jawi / khat at Tijarah Pintar Gallery, Johor Bahru - Malaysia. This model is one of the experiential learning that provides learning experiences in the form of providing services to the community. The hallmark of this model is the learning process that is integrated with field experience and the existence of a reflection process. The method used in this activity is a participatory method by involving partner students to formulate and analyze their writings and campus needs in accordance with the course. The results of the service show that service learning in learning Malay / Jawi / Kha Arabic writing has an impact on mastering better knowledge. This is due to the experience of direct observation at Tijarah Pintar Gallery, Johor Bahru - Malaysia related to the phenomenon that is the focus of the theory. In addition, critical and analytical thinking skills are also more trained through the process of reflection. Another thing that is also well developed, is a caring attitude and sensitivity to problems on campus.